1988
DOI: 10.1139/b88-324
|View full text |Cite
|
Sign up to set email alerts
|

Penetration and colonization of resistant and susceptible Apium graveolens by Fusarium oxysporum f.sp. apii race 2: callose as a structural response

Abstract: Root apices of Apium graveolens L. resistant and susceptible to race 2 of Fusarium oxysporum f.sp. apii (R. Nels. & Sherb.) were studied at various times after inoculation, using light and electron microscopy to determine structural response(s) of the hosts during penetration and colonization by the pathogen. Penetration was intercellular and intracellular and involved mechanical and enzymatic mechanisms. At the onset of penetration, the host cell walls manifested fluorescence, induced with either aniline … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
2
4
0
Order By: Relevance
“…The same but less intense and numerous defence reactions as described for the non-pathogenic strain have been observed in the root invaded by the pathogen : wall appositions and thickenings ; intracellular and intercellular deposits attached on hyphae ; and accumulation of granular plugs in the vessels. These defence reactions have been observed in other plant species infected by other formae speciales of F. oxysporum (Charest et al, 1984 ;Jordan et al, 1988 ;Tessier et al, 1990 ;Benhamou et al, 1990a). Based on our observations with F. oxysporum f. sp.…”
Section: supporting
confidence: 85%
See 1 more Smart Citation
“…The same but less intense and numerous defence reactions as described for the non-pathogenic strain have been observed in the root invaded by the pathogen : wall appositions and thickenings ; intracellular and intercellular deposits attached on hyphae ; and accumulation of granular plugs in the vessels. These defence reactions have been observed in other plant species infected by other formae speciales of F. oxysporum (Charest et al, 1984 ;Jordan et al, 1988 ;Tessier et al, 1990 ;Benhamou et al, 1990a). Based on our observations with F. oxysporum f. sp.…”
Section: supporting
confidence: 85%
“…This leads to the conclusion that both possibilities exist, and that depending on the strain studied, on the forma specialis and on the experimental conditions, one or the other possibility is predominant. This might explain why the research published to date is so confusing (Alconero, 1968 ;Smith & Peterson, 1983 ;Jordan et al, 1988 ;Farquhar & Peterson, 1989 ;Bhalla et al, 1992). Finally, this study supports the hypothesis that the pathogenic and the non-pathogenic F. oxysporum might compete for colonization of the root surface and the root tissues.…”
Section: supporting
confidence: 74%
“…In addition, mechanical penetration of the host has been reported in terrestrial associations, usually complementary to enzymatic penetration of the cuticle. An inward bending of the cuticle is characteristic of mechanical penetration (Politis & Wheeler, 1973;Jordan et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…Although no quantitative data were provided previously, it has been suggested that the penetration of F. oxysporum takes place in the root cap (Alconero 1968), in the meristematic zone (Bishop and Cooper 1983, Gerick and Huisman 1985, Farquhar and Peterson 1989, Smith and Peterson 1983 or in the elongation zone (Bhalla et al 1992, Jordan et al 1987. The root secretes exudates.…”
Section: Penetration By the Fungus In Different Toot Zonesmentioning
confidence: 99%